Local perceptions of degradation in rangelands from a livestock farming community in Chiapas, Mexico - Guevara Hernández, F.; Pinto, R.; Rodríguez, L.A.; Gómez, H.; Ortiz, R.; Cruz, Georgina; Ibrahim, Muhammad Akbar (2015)
Centro Agronómico Tropical de Investigación y Enseñanza (CATIE) - MAP